2007
DOI: 10.1590/s1807-59322007000200015
|View full text |Cite
|
Sign up to set email alerts
|

Urinary and Sexual Manifestations of Patients Infected by HTLV-I

Abstract: Oliveira P, Castro NM de, Carvalho EM. Urinary and sexual manifestations of patients infected by HTLV-I. Clinics. 2007;62(2):191-6. HTLV-I is considered to be a virus of low morbidity, since the principal diseases associated with this viral infection, HTLV-Iassociated myelopathy/tropical spastic paraparesis (HAM/TSP) and adult T-cell leukemia/lymphoma (ATLL), are observed in less than 5% of infected individuals. Urinary symptoms are frequent in patients with myelopathy and consist principally of nocturia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 22 publications
(27 reference statements)
3
44
0
3
Order By: Relevance
“…Previous studies have described that arthritis, urinary tract disorders, fibromyalgia, and major depression are frequently found in HTLV-1-infected populations (18,63,77,91). Possibly, some of these diseases either share a pathological mechanism with HTLV-1-related diseases or are related to psychological distress due to the infection.…”
Section: Htlv-1-associated Diseasesmentioning
confidence: 99%
“…Previous studies have described that arthritis, urinary tract disorders, fibromyalgia, and major depression are frequently found in HTLV-1-infected populations (18,63,77,91). Possibly, some of these diseases either share a pathological mechanism with HTLV-1-related diseases or are related to psychological distress due to the infection.…”
Section: Htlv-1-associated Diseasesmentioning
confidence: 99%
“…During the initial phases the most common urinary symptoms are nocturia, urge urinary incontinence and dysuria, progressing to feelings of micturition effort, incomplete bladder emptying and incontinence. 44,45,46 Erectile dysfunction is reported in 88.2% of patients with HAM/TSP, in comparison with a rate of 17% in the general population. 44 Rocha et al 47 observed symptoms suggestive of urinary infection in HTLV carriers, but did not confirm infection by urine culture in the majority of cases (81%).…”
Section: Erectile Dysfunction and Urinary Symptomsmentioning
confidence: 99%
“…These individuals, who also reported difficulty in using condoms, relayed the understanding that women should submit to their partner´s decisions on the grounds that this "passive" posture was suitable for females in a society still very marked by macho men behaviour [27][28][29]. However, men may have greater difficulty in the use of condoms because one of the first symptoms of HAM/TSP is erectile dysfunction [30]. Taken together, simply orienting the health team to indicate condom use to prevent transmission did not address the specific needs of these individuals.…”
Section: Resultsmentioning
confidence: 99%